Contamination characteristics, source apportionment, and health risk assessment of heavy metals in agricultural soil in the Hexi Corridor - Wang, Feifei; Guan, Qingyu; Tian, Jing; Lin, Jinkuo; Yang, Yanyan; Yang, Liqin; Pan, Ninghui (Catena (Giessen), 2020)
[Display omitted] •Geochemical baseline values of heavy metal in agricultural soil were evaluated.•The indexes of PI, EI and RI revealed that soil was moderately polluted wholly.•Apply geostatistical analysis, PMF and health risk model to obtain sources.•There were no significant carcinogenic and non-carcinogenic risk effects.•Agriculture, industry and traffic were the main and priority pollution sources. To determine the heavy metal contamination of agricultural soil in the Hexi Corridor, 376 soil samples were collected and analyzed for their heavy metal content. The geochemical baseline value (GBV), single-factor pollution index (PI), ecological risk of a single heavy metal, and comprehensive ecological risk index (RI) were used to assess the degree of pollution. Geostatistical analysis, positive matrix factorization (PMF), and a health risk assessment model were used to determine the primary sources of pollution and priority sources. Although the mean Ti, V, Cr, Mn, Fe, Ni, Cu, Zn, As, and Pb concentrations (2717, 62.85, 48.23, 511.6, 24827, 51.29, 26.47, 53.98, 12.39, 16.85 mg•kg−1 in the west, 3046, 72.15, 59.32, 598.1, 27614, 54.57, 29.55, 59.47, 13.63, 20.74 mg•kg−1 in the center, and 2558, 61.02, 39.67, 466.7, 22575, 39.94, 26.06, 54.81, 11.86, 20.38 mg•kg−1 in the east, respectively) did not exceed the national critical values, approximately 1% of the west As samples did exceed their critical values. The mean concentrations of the heavy metals were less than their corresponding GBVs. The PI and RI revealed that the agricultural soil was moderately polluted, at low ecological risk, and the least polluted in the center. Based on PMF, Factor 1 represented metal processing; Factor 2 represented the mixed sources of electroplating and smelting in the west and center, and the mixed sources of mining and agricultural activities in the east; Factor 3 was ascribed to agriculture; and Factor 4 was the mixed sources of atmospheric deposition and traffic emission. The main pollution source, Factor 4 in the west and east and Factor 2 in the center, had the highest percent proportion of total metals and priority pollution sources, thus contributing the most to the carcinogenic (Factor 2 in the west and Factor 3 in the center and east) and non-carcinogenic risks (Factor 2 for adults and Factor 1 for children in the west and Factor 3 in the center and east), respectively.